Writing Difficulties and Their Relationship to Speaking Anxiety among Primary School Students - Taha, Aslam Hussam (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify writing difficulties and their relationship to speech anxiety among primary school students in the center of Salah al-Din Governorate, Tikrit, and to know the statistically significant differences according to the gender variables (male - female). The researcher used the descriptive approach with a correlational relationship in his research because it is compatible with the nature of this study. The research sample consisted of 300 male and female students from the primary stage. The researcher prepared a writing difficulties scale, which consists of two dimensions: the first dimension is handwriting and the second dimension is dictation. The researcher adopted the Al-Aqidi scale (2013) for speech anxiety. To achieve the objectives of the research, the psychometric properties of validity and reliability were extracted using statistical methods, including Pearson’s correlation coefficient, the effect test for the single sample, and the t-test for two independent tests. The results showed the existence of statistically significant differences in the level of writing difficulties and speech anxiety among the sample members, the existence of statistically significant differences between males and females according to the gender variables males, and the existence of a statistically significant positive correlation between people who suffer from writing difficulties and people who suffer from speech anxiety